The Energy Cost of Running with the Ball in Soccer - Piras, Alessandro; Raffi, Milena; Atmatzidis, Charalampos; Merni, Franco; Di Michele, Rocco (International Journal of Sports Medicine, 2017)
Running with the ball is a soccer-specific activity frequently used by players during match play and training drills. Nevertheless, the energy cost (EC) of on-grass running with the ball has not yet been determined. The purpose of this study was therefore to assess the EC of constant-speed running with the ball, and to compare it with the EC of normal running. Eight amateur soccer players performed two 6- min runs at 10 km/h on artificial turf, respectively with and without the ball. EC was measured with indirect calorimetry and, furthermore, estimated with a method based on players’ accelerations measured with a GPS receiver. The EC measured with indirect calorimetry was higher in running with the ball (4.60±0.42 J/kg/m) than in normal running (4.19±0.33 J/kg/m), with a very likely moderate difference between conditions. Instead, a likely small difference was observed between conditions for EC estimated from GPS data (4.87±0.07 vs. 4.83±0.08 J/kg/m). This study sheds light on the energy expenditure of playing soccer, providing relevant data about the EC of a typical soccer-specific activity. These findings may be a reference for coaches to precisely determine the training load in drills with the ball, such as soccer-specific circuits or small-sided games.
Keywords: GPS; training load; energy expenditure